PERANAN MUSIK GEREJAWI SEBAGAI SARANA KOINONIA BAGI JEMAAT MASA KINI - Mardiandi Tanduk; Jeni Sembo, Julianti Liku Arruan, Astuti Karrang Bu'tu, Mariana (ADISAM PUBLISHER, 2026)
This research aims to delve into the role of church music as a means of koinonia for the contemporary congregation. Church music has the power to deepen social and spiritual bonds among congregation members, even serving as a source of encouragement during worship. However, there is still a lack of research specifically exploring this dynamic in the context of today's congregations. Through a holistic qualitative approach, this study explores individuals' experiences, perceptions, and interpretations of the role of church music in strengthening koinonia. Research methods employed include literature review, light interviews with congregation members and church leaders, participatory observation in worship activities, and content analysis of lyrics, melodies, and arrangements of church music. The findings indicate that church music plays a significant role in creating an atmosphere conducive to fellowship, connecting diverse cultural backgrounds and generations in spiritual unity, and enabling congregants to experience profound fellowship beyond social and cultural boundaries. The conclusion of this research underscores the importance of considering the role of church music in building a strong and united church community amidst dynamic societal changes.